Impact of Farmer Cooperatives on Labor Employment: Evidence from Rural China - Yutong Qiu; Yunli Bai; Jiaojiao Wu; Xuanye Zeng; Linxiu Zhang (Land)
Farmer cooperatives are one of the types of important entities for agricultural production and rural community development in China. This study aims to examine the effects of farmer cooperatives on rural labor employment and explores the mechanisms from the perspective of institutional advantage, factor redistribution, and value chain. Leveraging two-waved panel data from the China Rural Development Survey, a multinomial Logit model and Tobit model with panel data are adopted. The results show that farmer cooperatives significantly boost rural labor employment, with a more pronounced effect on fully farming and part-time farming. These effects are primarily seen through three mechanisms: income augmentation stemming from institutional advantages, factor redistribution by land transferring and technology service/adoption, as well as industrial clusters. The limited value chain extension of farmer cooperatives hinders its role in improving fully non-agricultural employment. The findings suggest that the government should support the high-quality development of farmer cooperatives to facilitate rural labor employment.